Overexpression of human NADPH:cytochrome c (P450) reductase confers enhanced sensitivity to both tirapazamine (SR 4233) and RSU 1069. - Patterson, A. V. (Nature Publishing Group, 1997)
P450 reductase (NADPH: cytochrome c (P450) reductase, EC 1.6.2.4) plays an important role in the reductive activation of the bioreductive drug tirapazamine (SR4233). Thus, in a panel of human breast cancer cell lines, expression of P450 reductase correlated with both the hypoxic toxicity and the metabolism of tirapazamine [Patterson et al (1995) Br J Cancer 72: 1144-1150]. To examine this dependence in more detail, the MDA231 cell line, which has the lowest activity of P450 reductase in our breast cell line panel, was transfected with the human P450 reductase cDNA. Isolated clones expressed a 78-kDa protein, which was detected with anti-P450 reductase antibody, and were shown to have up to a 53-fold increase in activity of the enzyme. Using six stable transfected clones covering the 53-fold range of activity of P450 reductase, it was shown that the enzyme activity correlated directly with both hypoxic and aerobic toxicity of tirapazamine, and metabolism of the drug under hypoxic conditions. No metabolism was detected under aerobic conditions. For RSU1069, toxicity was also correlated with P450 reductase activity, but only under hypoxic conditions. Measurable activity of P450 reductase was found in a selection of 14 primary human breast tumours. Activity covered an 18-fold range, which was generally higher than that seen in cell lines but within the range of activity measured in the transfected clones. These results suggest that if breast tumours have significant areas of low oxygen tension, then they are likely to be highly sensitive to the cytotoxic action of tirapazamine and RSU 1069. IMAGES: